EVOLUTIONARY TRANSFORMATION OF BIOLOGICAL DIVERSITY OF COASTAL ECOSYSTEMS IN CHANGING THE LEVEL CASPIAN SEA - G. M. Aburahmanov; S. M. Klycheva; G. A. Ahmedova; M. Z. Magomedova; Z. I. Soltanmuradova (Юг России: экология, развитие)
The results of study of the spiders fauna of Daghestan on 2011 were summed up at most in the work. The annotated lost of species was cited according to the world catalogue of Norman Platnik [1]. By the present time the composition of species of studied district includes 311 species, from which 59 species are cited as new for Daghestan, and 2 species (Drassodes arc-hibensis Ponomarev & Alieva, 2008, Drassodes dagestanus Ponomarev & Alieva, 2008) are described as new for science. The indicated specimen earlier as sp. are identified to species – the species Nurscia albosignata Simon, 1874, earlier was identified as Nurscia sp. [8], the species Clubiona alpicola Kulczynski, 1881, earlier was identified as Clubiona sp.[8], and the species Clubiona brevipes Blackwall, 1841, earlier was identified as Clubiona sp.[8]. The mistaken definition is corrected – the species Pirata hurkai Buchar, 1966, earlier identified as Pirata knorri (Scopoli, 1763).